Healthcare-Seeking Behavior and Associated Factors for Newborn Danger Signs among Mothers Who Gave Birth in the Last 12 Months in Anlemo District - Zeyene Abute Idris; Garumma Tolu Feyissa; Legesse Tesfaye Elilo; Markos Selamu Jifar; Aregash Mecha (Hindawi Limited, 2022)
Background. Healthcare-seeking behavior is referred to as any action taken by individuals who believe they have a health problem or are ill in order to find an appropriate remedy. The aim of this is to assess healthcare-seeking behavior on newborn danger signs and associated factors among mothers who gave birth in the last 12 months in the Anlemo district. Methods. A community-based cross-sectional study was conducted in the Anlemo district from June 15th, 2019 to July 16th, 2019. Data were collected from 421 randomly selected mothers through a face-to-face interview. Data were cleaned and entered into Epi-Data version 3.1, and then, exported to SPSS version 22.0 for analysis. Binary logistic regression with p values less than 0.25 was entered into a multivariable logistic regression for analysis. Finally, adjusted odds ratios (AOR) with 95% confidence intervals at a p value of <0.05 were considered as a statistically significant association with the outcome variable. Results. Among mothers whose newborns faced newborn danger signs, 34.5% (95% CI: 28.7, 40.5%) sought medical attention for newborn danger signs. When mothers were faced with neonatal danger signs, the multivariable logistic regression model identified three independent variables that were associated with their healthcare-seeking behavior. Mothers who had a college degree or above were 6.34 times more likely than mothers who could not read or write to seek medical care (AOR = 6.34, 95% CI: 1.23-32.69). Mothers or healthcare seekers who did not travel a long distance (less than 5 kilometers) to acquire healthcare were 2.53 times more likely than mothers who traveled a long distance (AOR = 2.53, 95% CI: 1.05-6.08), which had a significant association with the dependent variable. Conclusions. In this study, the proportion of mothers seeking care for newborn danger signs was low, and the mothers' education, time to reach the nearest health facility, and place of delivery were factors of statistical significance with the dependent variable.